2019
DOI: 10.1039/c9ra07490b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, magnetism and photocatalysis of α-Fe2O3nanosnowflakes

Abstract: α-Fe2O3 nanosnowflakes exhibit enhanced coercivity and improved photocatalytic performance for organic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Figure a shows the absorption spectra of the series of CV solutions (50 mL, 20 mg/L) in the presence of Fe-MOF-1 (10 mg) with H 2 O 2 (0.5 mL, 30%) under visible light with different irradiation times from 0 to 24 min. The maximum absorption of CV before irradiation is about 589 nm . When the light was on, the maximum absorption decreases sharply from 3.484 to 1.788.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure a shows the absorption spectra of the series of CV solutions (50 mL, 20 mg/L) in the presence of Fe-MOF-1 (10 mg) with H 2 O 2 (0.5 mL, 30%) under visible light with different irradiation times from 0 to 24 min. The maximum absorption of CV before irradiation is about 589 nm . When the light was on, the maximum absorption decreases sharply from 3.484 to 1.788.…”
Section: Resultsmentioning
confidence: 97%
“…The maximum absorption of CV before irradiation is about 589 nm. 47 When the light was on, the maximum absorption decreases sharply from 3.484 to 1.788. With the extension of irradiation time, the maximum absorption gradually decreases from 3 to 21 min and finally tends to zero at 24 min.…”
Section: Magnetic Properties Of Fe-mof-1mentioning
confidence: 99%
“…Photocatalytic degradation is considered to be a promising technology because ofits safe and sustainability [6] . It is reported that methyl violet was degraded by catalysts such as metal oxide (MnO 2 , [7] Mg‐doped ZrO 2 [8] and α‐Fe 2 O 3 , [9] ), metal composite (TiO 2 /ZnS, [10] Fe 0 @Guargum‐crosslinked‐soyalecithin hydrogel, [11] Co(II) thiocyanate complex [12] ), metal organic catalysts [13] and perovskite [14] . However, these materials are limited to metal‐involving compounds and some materials require complexpreparation process.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, as a photo-Fenton catalyst, α-Fe2O3 could initiate the photo-Fenton reaction under almost neutral conditions, eliminating the need to adjust the pH value at all times in the reaction process. On the other hand, Fe 3+ could be reduced to Fe 2+ by the electrons on the conduction band (CB) of α-Fe2O3, which reduces the loss of Fe 2+ and the production of solid sludge [14][15][16]. Nevertheless, a single α-Fe2O3 photocatalyst still exhibit poor photocatalytic activity due to the migration kinetics and sluggish separation of photogenerated carriers [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%